Virtual Assistant Avatars to Nudge Pro-Social Behavior: Exploratory Insights from a Co-Design Study - Rabab Ali Abumalloh (22788498) (2025)
Social media enhances connectivity and information exchange, but it also enables harmful behaviors, including cyberbullying and discrimination. Platform design can address these issues by encouraging prosocial behavior. Nudges: subtle design interventions that guide behavior without limiting choice, can be implemented through interface elements or advanced modalities such as virtual assistant avatars offering verbal or non-verbal feedback. This study adopts a co-design and exploratory approach to develop conceptual strategies for avatar-mediated nudges that promote prosocial behavior, focusing on gender equality and social inclusion. Thirteen Arab participants engaged in a co-design session, and the data were analyzed using thematic analysis. Four themes emerged: Positive Reinforcement, Uncanny Valley, Social Role, and Social Exchange. Findings indicate that preferences for avatar gender are shaped by cultural expectations and stereotypes, while desired levels of realism and anthropomorphism vary. They also evaluated the proposed interventions through a cost–benefit lens, offering guidance for designing acceptable avatar-mediated interactions. Other Information Published in: International Journal of Human–Computer Interaction License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/10447318.2025.2589499